Characteristics of scale deposition in gas-condensate wells - Воловецький, Володимир Богданович; Гнітко, Андрій Володимирович; Щирба, Оксана Миколаївна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. The article deals with one of many possible complications that may occur in the process of gas and gas-condensate wells operation. In fact, scale deposits can be observed in wells at all stages of field development. Scale deposition inside the tubing has a negative impact on hydrocarbons production. This causes the decline of gas production rate. The major factor of scale deposits formation is overtreatment of water solution with different salts and the effect of field hydrogeology. Thus, special methods are used in practice to prevent scale deposition and combat this complication. The purpose of the article. To define the causes of scale deposition, the detailed analysis of well operation should be performed that will help to take the appropriate prevention measures. Methods. The authors’ own achievements as well as the research results of domestic and foreign investigators made the methodical basis for the article. Results. The production data of the wells from different fields have provided the information about scale deposition. Many of the described ways of combating and eliminating scale deposits are expensive, their use causes well downtime and production decline. Therefore, it has been proposed to take easy-to-use preventive measures. Scientific novelty and practical significance. During investigation of the production researches results and calculations the specialists of UkrNDIgas proposed to classify the wells with reduced production capacities within the field into groups and categories according to the degree of total salinity of formation water. It has been proposed to control the process of scale deposition by the results of water analysis, taken from the wells. Each well has the set limit values of salinity. Based on the operation analysis of wells in different fields, the calculated predicted results of scale deposition in wells according to the existing procedures and their comparison with the factual data from production fields, the specialists of the institute have developed the efficient complex multi-faceted measures.